Providing Spiritual Care to In-Hospital Patients During COVID-19: A Preliminary European Fact-Finding Study - Timmins, Fiona; Connolly, Michael; Palmisano, Stefania; Burgos, Daniel; Mariano Juarez, Lorenzo; Gusman, Alessandro; Soriano, Vicente; Jewdokimow, Marcin; Sadlon, Wojciech; López, Aída; Conde Caballero, David; Campagna, Sara; et al. (Journal of Religion & Health, 2022)
Historically, there has be a close relationship between the nursing services and spiritual care provision to patients, arising due to the evolvement of many hospitals and nursing programmes from faith-based institutions and religious order nursing. With increasing secularism, these relationships are less entwined. Nonetheless, as nurses typically encounter patients at critical life events, such as receiving bad news or dying, nurses frequently understand the need and requirement for both spiritual support and religious for patients and families during these times. Yet there are uncertainties, and nurses can feel ill-equipped to deal with patients' spiritual needs. Little education or preparation is provided to these nurses, and they often report a lack of confidence within this area. The development of this confidence and the required competencies is important, especially so with increasingly multicultural societies with diverse spiritual and religious needs. In this manuscript, we discuss initial field work carried out in preparation for the development of an Erasmus Plus educational intervention, entitled from Cure to Care Digital Education and Spiritual Assistance in Healthcare. Referring specifically to post-COVID spirituality needs, this development will support nurses to respond to patients' spiritual needs in the hospital setting, using digital means. This preliminary study revealed that while nurses are actively supporting patients' spiritual needs, their education and training are limited, non-standardised and heterogeneous. Additionally, most spiritual support occurs within the context of a Judeo-Christian framework that may not be suitable for diverse faith and non-faith populations. Educational preparation for nurses to provide spiritual care is therefore urgently required.
Keywords: spirituality; religion; faith; education; nurses; healthcare workers; health; JCR; Scopus